Aquatic and edaphic determinants influencing carbon storage in a salt marsh grass, Porteresia coarctata, of the Bhitarkanika wildlife sanctuary and the Mahanadi estuary. Issue 4 (12th March 2021) - Banerjee, Kakoli; Mallik, Kapileswar; Sahoo, Chandan Kumar; Paul, Rakesh
Abstract: In the present study, investigation was carried out in the Bhitarkanika and Mahanadi mangrove ecosystems during 2017–18 and 2018–19 on biomass and carbon of Porteresia coarctata, a salt marsh grass species of the Poaceae family. Water parameters such as temperature, pH, and salinity were measured along with soil parameters such as pH, electrical conductivity, bulk density, organic carbon, and soil texture, which were measured simultaneously. Growth pattern in terms of increase in biomass and carbon (in Mg ha −1 ) over the study period in Bhitarkanika was 1.03 ± 0.49 and 0.48 ± 0.22 and that of Mahanadi was 0.62 ± 0.17 and 0.29 ± 0.09, respectively. The correlation coefficient was computed for biomass and carbon of P. coarctata where salinity, soil bulk density, and soil organic carbon played a major role in governing the distribution of species. MANOVA results computed for both Bhitarkanika and Mahanadi showed significant difference between stations for both biomass and carbon of P. coarctata . However, other parameters of water and soil exhibited very weak relationship. Allometric models computed with AGB and AGC as dependent variables and physico‐chemical variables as independent variables have revealed that salinity and OC are the major driving factors for growth and development as well as carbon storage potential of the species.